A State Feedback Controller Based on GCC Algorithm against Wind-Induced Motion for High-Rise Buildings with Parametric Uncertainties. (14th July 2019) - Li, Zuohua; Chen, Chaojun; Teng, Jun; Dong, Junkai; Lin, Beichun
Abstract : High-rise buildings with an active mass damper/driver (AMD) system generally use a simplified mathematical model. The result leads to parametric uncertainties including the stiffness and mass variations exist, and the accuracy of its controller is seriously affected. In view of the above uncertainties, based on a Lyapunov stability theory and linear matrix inequality (LMI) approach, a state feedback controller based on the guaranteed cost control (GCC) algorithm is proposed in this paper. A ten-storey frame with an AMD system is taken as a numerical example, and its control effect and AMD parameters are viewed as the control indexes. The performance of the proposed robust controller is compared with a conventional controller based on the classical LQR algorithm. The analysis results show that the new controller effectively suppresses the dynamic responses of high-rise buildings with parametric uncertainties and keeps the AMD parameters stable. Finally, a four-storey steel experimental frame with an AMD system is used to verify the correctness of the conclusions.